2020
DOI: 10.1177/1932296820906888
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Insulin Degludec/Liraglutide (IDegLira) Compared With Basal-Bolus Insulin Therapy is Consistent Across Participant Subgroups With Type 2 Diabetes in the DUAL VII Randomized Trial

Abstract: Background: Insulin degludec/liraglutide (IDegLira) results in glycated hemoglobin (HbA1c) levels comparable with basal-bolus (BB) therapy. Here, we assessed the effect of once-daily IDegLira compared with BB (once-daily insulin glargine 100 U/mL and insulin aspart ≤4 times/day) across subgroups with varying characteristics. Materials and Methods: DUAL VII trial participants (type 2 diabetes [T2D], HbA1c 53-86 mmol/mol [7.0%-10.0%]) were subgrouped post hoc based on the following baseline characteristics: HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…25 Benefits of IDegLira have also been preserved across subgroups in the DUAL VII study with similar HbA1c reductions, less severe or plasma glucose-confirmed hypoglycaemia, lower end-of-trial total daily insulin dose, together with weight loss relative to meal-time plus basal insulin therapy. 26 The main limitations of the present analysis are, firstly, the exploratory nature of the assessments except for the between-treatment differences in HbA1c and body weight changes in the basal insulin dose and BMI subgroups. However, the data used were entirely those of the original database, and the endpoints were those specified for the main study analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…25 Benefits of IDegLira have also been preserved across subgroups in the DUAL VII study with similar HbA1c reductions, less severe or plasma glucose-confirmed hypoglycaemia, lower end-of-trial total daily insulin dose, together with weight loss relative to meal-time plus basal insulin therapy. 26 The main limitations of the present analysis are, firstly, the exploratory nature of the assessments except for the between-treatment differences in HbA1c and body weight changes in the basal insulin dose and BMI subgroups. However, the data used were entirely those of the original database, and the endpoints were those specified for the main study analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Similar findings were reported in the LixiLan‐O study in insulin‐naïve participants (iGlarLixi vs. insulin glargine 100 U/mL) across subgroups, except for the possibility of higher incidence of hypoglycaemia in the HbA1c ≥64 mmol/mol (≥8.0%) versus <64 mmol/mol subgroup, attributed to differences in dosing 25 . Benefits of IDegLira have also been preserved across subgroups in the DUAL VII study with similar HbA1c reductions, less severe or plasma glucose‐confirmed hypoglycaemia, lower end‐of‐trial total daily insulin dose, together with weight loss relative to meal‐time plus basal insulin therapy 26 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data on demographic characteristics, hematochemical analyses and medications at the last available follow-up were collected. Good control of DM was defined as having fasting glucose <130 mg/dl or HbA1c < 53 mmol/mol ( IDF Clinical Practice Recommendations for, 2017 ; Billings et al, 2021 ). Hypercholesterolemia was defined as being on a lipid-lowering medication and having low-density lipoproteins (LDL) > 100 mg/dl.…”
Section: Methodsmentioning
confidence: 99%
“…IDegLira recipients also had fewer hypoglycaemia events per person-year of exposure vs individuals receiving insulin glargine uptitration (Table 1) [59]. Results from the DUAL VII study showed that IDegLira was non-inferior to basal-bolus insulin treatment (insulin glargine plus insulin aspart) in reducing HbA 1c (P < 0.0001 for non-inferiority) among individuals with inadequate glycaemic control on insulin glargine plus metformin (Table 1) [60]. Similar proportions of participants achieved HbA 1c goals of <53 mmol/mol (<7.0%) and ≤48 mmol/mol (≤6.5%) with both treatments.…”
Section: Fixed-ratio Formulationsmentioning
confidence: 99%